2021
DOI: 10.3390/su13115964
|View full text |Cite
|
Sign up to set email alerts
|

Credit Constraint and Rural Household Welfare in the Mezam Division of the North-West Region of Cameroon

Abstract: The purpose of this study is to examine the effect of the rural household’s head and household characteristics on credit accessibility. This study also seeks to investigate how credit constraint affects rural household welfare in the Mezam division of the North-West region of Cameroon. Using data from a household survey questionnaire, we found that 36.88% of the households were credit-constrained, while 63.13% were unconstrained. A probit regression model was used to examine the determinants of households’ cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The Northwest region comprises 7 Divisions including Boyo, Bui, Donga-Mantung, Menchum, Momo, Ngoketunjia, and Mezam Division. Mezam Division is constituted of 7 Subdivisions which include: Bamenda I, Bamenda II, Bamenda III, Bafut, Bali, Santa, and Tubah (Atamja & Yoo 2021).…”
Section: The Study Sitementioning
confidence: 99%
“…The Northwest region comprises 7 Divisions including Boyo, Bui, Donga-Mantung, Menchum, Momo, Ngoketunjia, and Mezam Division. Mezam Division is constituted of 7 Subdivisions which include: Bamenda I, Bamenda II, Bamenda III, Bafut, Bali, Santa, and Tubah (Atamja & Yoo 2021).…”
Section: The Study Sitementioning
confidence: 99%
“…One frequently used measure of welfare is household consumption and consumption expenditure, and a number of studies have found credit access to have positive impacts on the measure (Attanasio et al, 2015;Bocher et al, 2017;Fink et al, 2020;Kaboski & Townsend, 2011;Mallick & Zhang, 2019;Meager, 2019;Song et al, 2020). This impact has been observed in various contexts, including in the Mezam district of North-West Cameroon where Atamja and Yoo (2021) found that households that either save formally or informally increase their consumption level, and hence their welfare. Access to finance has also been found to have positive impacts on overall household expenditure in India (Shetty, 2008), household investment in Thailand (Gloede & Rungruxsirivorn, 2013), income (Addury, 2018;Ibrahim & Aliero, 2020;Shetty, 2008), as well as assets and empowerment (Nanziri, 2018;Shetty, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A key impeding factor for local production is the extremely limited access of farmers to microcredit. A recent study in the Northwest Region of Cameroon suggests that almost 37% of (mostly farming) households are creditconstrained, while 63% are not (Atamja and Yoo, 2021).…”
Section: Introductionmentioning
confidence: 99%